Pengaruh Pendapatan Orang Tua, Pendidikan Orang Tua, Kecerdasan Intelektual, Perencanaan Karir dan Efikasi Diri Terhadap Minat Melanjutkan Pendidikan Tingkat Perguruan Tinggi Siswa Kelas XII SMA N 16 Padang - Devi, Risna; Jolianis, Jolianis; Dahen, Lovelly Dwinda (Jurnal Horizon Pendidikan, 2022)
This study aims to analyze the influence of parental income, parental education, intellectual intelligence, career planning and self-efficacy on students' interest in continuing their education at the college level. The results of data analysis in this study found that there was an influence of variables of parental income, parental education, intellectual intelligence, career planning and self-efficacy together on the interest in continuing education at the class XII college level at SMAN 16 Padang. Pervariable results can be described based on two levels as follows: First, students who have planned detailed ideals, namely the probability value of the parental income variable (0.013, parental education (0.018), career planning (0.008) and self-efficacy (0.011) affect the interest in continuing higher education which can be proven with a probability value smaller than α (0.05). As for the probability value of intellectual intelligence (0.619) it has no effect on the interest in continuing higher education as evidenced by the probability value greater than 0.05. Second, students who have not planned the goals that can be detailed, namely the probability value of the parental income variable (0.048), parental education value (0.026), career planning (0.013) and self-efficacy (0.033) affect the interest in continuing higher education which can be proven by the probability value of each less than α (0.05). As for intellectual intelligence, the sig value (0.261) has no effect on the interest in continuing college-level education as evidenced by the probability value of each of them greater than α (0.05).